2014
DOI: 10.1136/lupus-2014-000015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced response to Epstein–Barr virus antigens by T-cells in systemic lupus erythematosus patients

Abstract: ObjectiveEpstein–Barr virus (EBV) has for long been associated with systemic lupus erythematosus (SLE). In this study, we investigated the levels of latent and lytic antigen EBV-specific T-cells and antibodies in SLE patients.MethodsT cells were analyzed by flow cytometry and antibodies were analyzed by enzyme-linked immunosorbent assay.ResultsSLE patients showed a significantly reduced number of activated (CD69) T-cells upon ex vivo stimulation with EBV nuclear antigen (EBNA) 1 or EBV early antigen diffuse (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 52 publications
8
55
4
Order By: Relevance
“…Besides, T‐cell activation is a fundamental step for the onset of the adaptive immune response. In this regard, CD69 is thought to be among the earliest surface markers of T‐cell activation, and its changes are correlated with SLE disease activity . In fact, active SLE patients show increased CD69 expression levels in comparison with inactive patients and healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, T‐cell activation is a fundamental step for the onset of the adaptive immune response. In this regard, CD69 is thought to be among the earliest surface markers of T‐cell activation, and its changes are correlated with SLE disease activity . In fact, active SLE patients show increased CD69 expression levels in comparison with inactive patients and healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical characteristics of all patients and controls are outlined in Table 1 . SLE patients and HCs have previously been reported on in the study by Draborg et al [ 17 ] as well as RA patients in the study by Troelsen et al [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies demonstrated that the EBV-dUTPase: (i) induce the secretion of the pro-inflammatory T H 1/T H 17 cytokines IL-6, IL-1β and type-I IFN in a TLR2dependent manner [17,18,21], (ii) up-regulates the expression of the inflammatory BIC/microRNA-155 [18], and (iii) alters EBV-specific CD8+ T-cell function by up-regulating the expression of several genes involved with the antiviral immune response [18]. These findings have also been reported in patients with SLE [13][14][15]22]. The data presented in this study demonstrate that the EBV-dUTPase may play a role in the immune over-reactivity observed in a subset of patients with LN by triggering abnormal innate and adaptive immune responses thus, inducing an immune amplification cascade that promotes autoimmunity.…”
Section: Issn: 2378-3672mentioning
confidence: 53%
“…Other studies demonstrated that antibodies directed against Epstein-Barr nuclear antigen 1 (EBNA-1) cross react with autoantigens associated with SLE [11] as well as dsDNA [12]. Furthermore, an increased EBV viral load in SLE patients was also demonstrated [13][14][15]. Whether or not the increased viral titers and EBV-specific immune responses observed in SLE reflect the sensitivity of the virus to perturbations in the immune system in these patients [16], and thus, represent a consequence of SLE rather than its cause, remains a topic of controversy.…”
mentioning
confidence: 99%